PERMAINAN TRADISIONAL ANAK-ANAK SUMATRA BARAT DALAM KARYA SENI GRAFIS - NURUL ILHAM, Drs. Ariusmedi, M.Sn., Drs. Yusron Wikarya, M.Pd. (Serupa The Journal of Art Education, 2018)
The creation of this final work aims to visualize the traditional games of West Sumatra children in graphic arts. showing the atmosphere of children in traditional games, which are now rarely seen. The method and process of work used in the creation of graphic art works through several stages: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization of Concepts, (5) Settlement. The results of the visualization of West Sumatra children's games in this graphic work are 10 works with the title: (1) Badie balantak, (2) Congkak, (3) Kelereng, (4) Ula nago, (5) Cik mancik, (6) Tali, (7) Gasiang, (8) Ketapel, (9) Kaki panjang, (10) Layang-layang.Kata kunci: permainan, tradisional, anak-anak, seni grafis.